In-circuit characterisation of device's impedance for signal integrity analysis - Chang, Richard Weng Yew (2011)
Rapid advances in integrated circuits (ICs) and process technology coupled with surge in consumers’ expectation for powerful processing capabilities and features dramatically change the way for digital circuit designs. With increasing clock speed and shorter rise time, impedance control for interconnects on the printed circuit board (PCB) to ensure good signal integrity (SI) performance has become a critical factor in high-speed digital design. Besides impedance control of interconnects on PCB, it is also equally important to be equipped with the knowledge of input and output impedances of the devices that will be connected to these interconnects. Any slight impedance mismatch will have an impact on the SI performance of the high-speed digital circuit. To achieve optimal impedance matching at the digital interfaces, one could only rely closely on the recommended equivalent circuit model of the interface from the manufacturer’s datasheet. However, the datasheet is usually suitable for specific application, layout and operating condition. Alternatively, one could utilise circuit simulation together with Input and Output Information Specifications (IBIS) model for input/output (I/O) interface impedance matching, which is straightforward but it provides only an approximate model. For more accurate equivalent interface model, three-dimensional (3D) full-wave modelling tool can be employed but it requires knowledge on the device’s internal details, which is often guarded by proprietary issues. Based on a two-probe inductive coupling approach, the thesis presents a novel in-circuit measurement method to characterise the impedance of any device (either passive or active) under its actual operating condition. With this in-circuit measurement setup, the impedance of a device can be characterised under intended operating conditions with specifics biasing current, voltage and operating frequency. The accurate and complete electrical characteristic extracted enables proper choice of termination component to achieve optimal SI performance in high-speed digital design with confidence.